736 Optimal Time for Cholecystectomy After ERCP. (4th May 2021) - Ibrahim, R; Abdalkoddus, M; Yao, L; Franklyn, J; Zainudin, N; Aroori, S
Abstract: Introduction: Recent research on the management of cholecystolithiasis with co-existing choledocholithiasis suggests performing cholecystectomy within 24 hours after ERCP has favourable outcomes. However, this target can be difficult to achieve in the NHS due to limited resources. Method: This retrospective study includes 444 patients who underwent successful ERCP before cholecystectomy. We examined the impact of the duration of ERCP to cholecystectomy and post ERCP complications on operative difficulty and patient outcomes. We also report on gallstone related readmissions and rate of retained stones. Results: The median duration from ERCP to cholecystectomy was 75 days, with a 14% readmission rate between their first successful ERCP and cholecystectomy. Our analysis showed a statistically significant negative correlation between ERCP-to-cholecystectomy duration and postoperative stay. Readmissions increased with time, but this did not reach statistical significance. The occurrence of post ERCP complications significantly increased postoperative stay and the open conversion rate. Conclusions: In contrast to recent research, our analysis suggests that early cholecystectomy post ERCP is not associated with better outcome. However, the impact of gallstone related readmissions needs further analysis. Post ERCP complication could serve as a predictor for operative difficulty and longer postoperative stay. It should be considered when planning the cholecystectomy.